Student Achievement and Middle Level Programs, Policies and Practices in Rural America: The Case of Community-Based Versus Consolidated Organizations - David Hough; Toni Sills-Briegel (Journal of Research in Rural Education, 1997)
Recent debate has centered on the role ofmiddle schools in rural areas. While some policymakers have focused on the organizational aspects ofmiddle schools, especially those characteristics that have defined middle schools in cities and suburbs, others have focused on creating optimal learning environments with attention to curriculum, instruction, and assessment. In this article, community-based and consolidated school organizations are analyzed and suggestions made about he most appropriate setting for young adolescents in rural communities.